Assessment of Soil Respiration Under Different Land Use in East Kutai, Indonesia - Komara, Liris Lis; Sulastri, Eka; Murtinah, Veronika; Sasmita, Nanang (Universitas Panji Sakti, 2025)
Forest areas are where the most advanced water and air cycles occur and cannot be replaced by any man-made products. For this reason, Indonesians' lives and forest lands are inextricably linked as economic resources. Deforestation also occurs at a considerable rate in East Kutai Regency. Changes in the area of forest land, which is continuously decreasing, followed by a growth in land area for other uses, including mining and plantations, serve as examples of this circumstance. To determine whether the conversion of this area is genuinely balanced between measures to protect the environment and the health of the soil and its economic value, more research must be done. One way to find out is to examine soil respiration in several locations. The purpose of the research was to compare soil respiration levels in three types of land cover in East Kutai Regency. The data collection method involves taking 0 – 30 cm depth of soil sample at three points in three locations, namely Rubber plantation, Teak plantation and Botanical Gardens. The total soil microorganism count is determined by soil organic carbon. The overall number of soil microorganisms increases with soil organic matter. Next, the soil samples are tested in the laboratory for colony total number. The study's findings indicated that the teak plantation had the lowest soil respiration, at21.37±0.9, and the Botanical Garden location had the highest, at29.87±1.91. The high total number of soil microorganisms makes respiration high because it produces high CO2, which is caused by the high activity of the microorganisms in the soil.